Revealed meta-preferences : axiomatic foundations of normative assessments in the capability approach - Silva-Leander, S (Oxford Poverty & Human Development Initiative (OPHI), 2011)
This paper explores the possibility of defining a non-utilitarian normative standard for assessments of welfare and deprivation. The paper contributes to this end in three ways. First, the paper formalises a key aspect of Prof. Sen’s critique of the assumption of consistent utility maximisation in the revealed preference theory. Secondly, the paper explores alternative formulations of the axiom of revealed preferences that are consistent with Prof. Sen’s critique and proposes a set of intuitive assumptions to characterise the relation between observed choices and underlying references in the absence of consistent utility maximisation. Finally, we use these to construct two alternative normative ranking rules that can be used in non-utilitarian welfare economics.